Efektifitas Pembelajaran Al-Qur’an Terhadap Kualitas Bacaan Al-Qur’an Siswa Di Sekolah SMP Muhammadiyah 50 Medan - Nur Fadhila (Yayasan Rahmat Islamiyah, 2023)
The purpose of this study was to determine how the effectiveness of learning the Qur'an on the quality of reading the students of SMP Muhammadiyah 50 Medan. This research method uses a quantitative approach with a sample of 57 students, with data collection techniques using observation, questionnaires, and documentation. The results of this study showed that based on the T test, the influence of al-Qur'an tutoring program variables on the quality of students 'reading of the Qur'an (Ha), al-Qur'an tutoring program variables (x) have a positive effect on the quality of students' reading of the Qur'an.